The Tahuantinsuyo: The political space and the useful body in the works of Martín de Murúa and of Guaman Poma de Ayala - Valdano, Clara Verónica (2011)
In this study I make a comparison between the General Peruvian History (1590, 1614) by Martín Murúa, and the New Chronicle and Good Government (1615) by Guamán Poma de Ayala. This comparison is based on textual and visual analysis of the construction of the body and space. Murúa tries to create a history according to the traditional Western idea, thus he aims to inform Spain about Peru. In Murúa, the mitmas and the chasquis are bodies that served as military tools to keep the space of the Tahuantinsuyo in order. It reveals that the mitmas and the chasquis are strategies that provide mobility and expandability to the Inca State. While Guamán Poma de Ayala builds the Tahuantinsuyo, the mitmas and the chasquis aiming to show the ability of the Andean peoples to govern themselves by means of advanced military and communicationsystems, Guamán Poma makes use of these aspects as an example of their resistance to the colonial government. Murúa, however, illustrates that these systems are kept, but at the service of the Spanish rule. In this study I start from the theory of Lefebvre, who emphasizes that the bodies set up various social practices that transform this space (27-41). Grosz also illustrates that the body functions as a place of social, political, cultural and geographical registration (23). Therefore, the space and the body are shaped in accordance with an established ideology, where the political, social and work colonial relationships show the constitution of an order.